Arsenic and fluoride contamination in the Independence Basin Aquifer System of Guanajuato, Mexico - Shepherd, Forest Thomas (Kansas State University, 2018)
Elevated concentrations of arsenic (As) and fluoride (F) have been documented within the volcano-sedimentary aquifers of the Independence Basin Aquifer System in Guanajuato, Mexico which lies in the Mesa Central (MC) physiographic province on the northern edge of the Trans Mexican Volcanic Belt (TVMB). The geogenic sources of these contaminants are not well understood. This study adds to the existing record of the distribution of As and F contamination in the major aquifers of the basin by analyzing 24 water samples from five urban and rural areas. The mean As and F concentrations in the Cuenca Alto Rio Laja (CARL) aquifer on the western side of the basin were ~10 µg/L (median = 36 µg/L) and ~0.5 mg/L (median = 0.8 mg/L), respectively. In contrast, the mean As and F concentrations in the Laguna Seca (LS) aquifer on the eastern side of the basin were ~44 µg/L (median = 11 µg/L) and ~5.8 mg/L (2.6 mg/L), respectively. The high sodium, alkalinity, and low calcium concentrations observed in both aquifers are typical for fractured acid volcanic geothermal systems which have been observed in many Mexican states. Boron, lithium, and groundwater temperature showed positive correlations with As (R² = 0.47, 0.68, and 0.55) and F (R² = 0.31, 0.73, and 0.57) concentrations. These trace elements and elevated groundwater temperatures are indicators of water with hydrothermal origins. The drill cuttings from two boreholes ~500 m in depth were analyzed by X-ray diffraction, petrographic, and elemental analysis. This work revealed that the volcanic rocks of the CARL aquifer are primarily comprised of plagioclase, quartz, potassium-feldspar, calcite, volcanic glass, apatite, and iron oxyhydroxides. Additionally, there are layers of volcanic rocks comprised of pyroxene, plagioclase, quartz; amphibole, biotite, and apatite. The sedimentary rocks of the LS aquifer are comprised primarily of plagioclase, potassium feldspar, muscovite, biotite, volcanic glass, apatite, calcite, and quartz. These sedimentary rocks were deposited on volcanic rocks comprised of plagioclase, pyroxene, quartz, calcite, apatite, olivine, amphibole, hematite, chlorite, biotite, and ilmenite. To determine source zones the distribution of leachable F from the drill cuttings of both boreholes was examined through batch reactors. The leached F concentration profile revealed that the upper 140 m and lower 400 m of the western and eastern sides of the basin were the dominant source zones of leachable F. Overpumping in the IBAS has caused water table levels in this aquifer the decline over time. As these groundwater wells continue to be constructed to deeper depths to reach groundwater the release of As and F from these sources and the mechanisms controlling As and F from these subsurface lithologies needs to be understood. The release of both As and F from the rocks of the western and eastern side of the basin at 400 to ~500 m depths were examined through pH-adjusted batch reactors with groundwater from the CARL which contained initial As and F concentrations of ~7.9 µg/L and ~0.8 mg/L; respectively. The dissolution of F-bearing minerals and adsorption reactions with iron oxyhydroxides display a dominant control on the changes in As and F concentrations in the groundwater of the CARL aquifer. At pH 5, the rocks from the 400 – 500 m depth within the CARL aquifer reduced the initial concentrations of As and F to values of ~5.8 µg/L and ~0.5 mg/L, respectively, after 200 hours. Whereas at a pH of 9 these rocks leached F increasing its concentration to ~0.9 mg/L. The As concentration was reduced to ~6.3 µg/L. In contrast to the CARL aquifer rocks, the rocks of the LS aquifer released F at all three pH values as F-bearing minerals dissolved. Alongside F-bearing mineral dissolution, adsorption on to iron oxyhydroxide surfaces could be occurring as F concentrations continuously decreased after 50 hours of reaction. The As concentrations in the rocks from the 400 – 550 m depths of the LS aquifer released minor amounts of As at pH 7 and 9, increasing the concentration slightly until 50 hours of reaction. During the remaining 150 hours of reaction the As concentrations displayed a continuous decrease in concentration. At pH 5, however, As concentrations decreased to ~5.7 µg/L after 200 hours of reaction. The spatial and kinetic leaching patterns observed in this study, combined with the mapping of known As- and F-bearing minerals within major rock aquifer groups on the east and west side of the basin, will suggest initial release or mobilization mechanisms to future researchers. The mechanisms of initial release and transport of As and F through aquifers of the Independence Basin should be studied through a combination of laboratory experiments and reactive flow and transport modeling to determine the migration of As and F from source rocks to groundwater wells.
Keywords: Arsenic; Fluoride; Independence Basin Aquifer System; Adsorption; Dissolution